Intercellular Signalling in the Mammary Gland 1995
DOI: 10.1007/978-1-4615-1973-7_26
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Hormonal Regulation of Wnt Gene Expression in the Mouse Mammary Gland

Abstract: Claudins are a large family of membrane proteins whose classic function is to regulate the permeability of tight junctions in epithelia. They are tetraspanins, with four alpha-helices crossing the membrane, two extracellular loops, a short cytoplasmic N-terminus and a longer and more variable C-terminus. The extracellular ends of the helices are known to undergo side-to-side (cis) interactions that allow the formation of claudin polymers in the plane of the membrane. The extracel-lular loops also engage in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(49 citation statements)
references
References 2 publications
6
42
0
1
Order By: Relevance
“…20,21 Normal epithelium, where it existed adjacent to tumour, showed weak staining, in accordance with data showing that, while several members of the Wnt gene family have been found to be expressed in the developing mammary gland, Wnt1 itself has not. 22,23 In contrast, in-situ tumour was immunostained intensively, an observation which suggests that Wnt1 is activated in premalignant stages of breast tumorigenesis, and which is in agreement with the findings from in vitro and in vivo experiments. Thus, Wnt1 expression was found to be insufficient for tumorigenesis in mouse mammary epithelial cell lines 24 and, furthermore, genetically altered mice expressing Wnt1 were reported to develop lobulo-alveolar hyperplasia rapidly, and subsequently focal carcinoma, after a long latency period.…”
Section: Discussionsupporting
confidence: 89%
“…20,21 Normal epithelium, where it existed adjacent to tumour, showed weak staining, in accordance with data showing that, while several members of the Wnt gene family have been found to be expressed in the developing mammary gland, Wnt1 itself has not. 22,23 In contrast, in-situ tumour was immunostained intensively, an observation which suggests that Wnt1 is activated in premalignant stages of breast tumorigenesis, and which is in agreement with the findings from in vitro and in vivo experiments. Thus, Wnt1 expression was found to be insufficient for tumorigenesis in mouse mammary epithelial cell lines 24 and, furthermore, genetically altered mice expressing Wnt1 were reported to develop lobulo-alveolar hyperplasia rapidly, and subsequently focal carcinoma, after a long latency period.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies suggested that Wnt4 is expressed only concomitant with high progesterone secretion in the adult and pregnant mammary gland (Gavin & McMahon, 1992;Weber-Hall et al, 1994). The finding that deletion of Wnt4 affected mammary regeneration potential more severely than abrogation of PR signaling suggested that Wnt4 may have PR-independent functions in stem cell stimulation.…”
Section: Control Of Wnt4 Expressionmentioning
confidence: 99%
“…Wnt genes have been suggested to play key roles in glandular development, including the induction of mouse mammary glands (Gavin & McMahon, 1992;Weber-Hall et al 1994). Evidence in favour of this suggestion comes from the regulated expression of these genes in mammary development as well as their proliferative effects on mammary epithelial cells when overexpressed (Wong et al 1994;Bradbury et al 1995).…”
Section: Introductionmentioning
confidence: 99%